Sociability, Religiosity and New Cosmovisions in Costa Rica at the turn of the Nineteenth to Twentieth Centuries - Martínez Esquivel, Ricardo (2013)
This paper intends to analyze Freemasonry’s role in the genesis of new cosmovisions based on its relationship with religiosity, atheism, spiritism, the Theosophy Society, co-Freemasonry and the Liberal Catholic Church (LCC) in Costa Rica during the turn of the 19th to 20th centuries. What were the social practices of Freemasons’ ideals regarding religiosity and the new cosmovisions? And how did they influence the enormous modernization process that the country was going through at that time? These are questions to answer through a prosopography analysis. Prosopography allows us to approach the relations between the structure and social dynamics of a group of Freemasons, as well as the social reality and the context of Costa Rica in which they took place. This not only allows us to approach Freemasonry with a greater understanding, but also to view Costa Rica as a country that was fully in the process of social changes and building cultural practices, as well as discourses.